Women's fasting habits and dietary diversity during Ramadan in rural Bangladesh - Andrea U. Seiermann; Hudaalrahman Al‐Mufti; Jillian L. Waid; Amanda S. Wendt; Shafinaz Sobhan; Sabine Gabrysch (Wiley, 2021)
Abstract Little is known about fasting practices and dietary changes during Ramadan in low‐ and lower‐middle‐income countries. Although pregnant women are exempt from fasting, they may still fast. This is of interest as dietary habits during pregnancy may affect the development of the unborn child. In a community‐based sample of young women in rural Sylhet division, Bangladesh, we described fasting practices and beliefs (n = 852). We also examined reported food group consumption and minimally adequate dietary diversity for women (MDD‐W) by Ramadan occurrence (n = 1,895) and by fasting adherence (n = 558) using logistic regression with Hindu women as a seasonal control. During Ramadan in 2018, 78% of pregnant Muslim women fasted every day. Over 80% of Muslim women believe that they should fast during pregnancy and over 50% expect positive health effects on the mother and the unborn child. We found strong evidence that Muslim women have more diverse diets during Ramadan, with higher odds of MDD‐W (OR [95% CI]: 5.0 [3.6, 6.9]) and increased consumption of pulses, dairy, fruit, and large fish. Dietary diversity increased to a lesser extent on non‐fasting days during Ramadan. Ramadan appears to improve dietary quality in both fasting and non‐fasting Muslim women in a rural population in Bangladesh. These results help to interpret findings from studies on Ramadan during pregnancy on later‐life outcomes and thus contribute to a better understanding of intrauterine influences of maternal nutrition on healthy child development.